Maternal diet during lactation and breast-feeding practices have synergistic association with child diet at 6 years. Issue 2 (10th July 2019) - Beckerman, Jacob P; Slade, Emily; Ventura, Alison K
Abstract: Objective: Children breast-fed during infancy consume more fruits and vegetables than formula-fed children. This pattern is likely due, in part, to infant learning from flavours of the mother's diet transmitted through breast milk, but more research is needed to understand associations between early flavour exposures and later dietary patterns. We examined whether breast-feeding and maternal fruit and vegetable consumption during nursing were synergistically associated with higher child fruit and vegetable consumption. Design: Prospective cohort study of breast-feeding duration, maternal diet postpartum and child diet. Complete breast-feeding and maternal diet data were available for 1396 mother–child dyads; multiple imputation was used for missing data in other variables. In separate multivariable logistic regression models, we estimated the adjusted odds of high child fruit or vegetable consumption at 12 months or 6 years as a function of breast-feeding duration, maternal fruit or vegetable consumption during nursing, and their interaction. Setting: The Infant Feeding Practices Study II and Year 6 Follow-Up. Participants: Mother–child dyads followed from birth to 6 years during 2005–2012 in the USA. Results: Longer breast-feeding duration was associated with high child fruit and vegetable consumption at 12 months. At 6 years, the interaction between breast-feeding duration and maternal vegetable consumption was associated with high child vegetable consumption. Conclusions: Higher maternal vegetable consumption and longer breast-feeding duration were synergistically associated with high child vegetable consumption at 6 years, independent of sociodemographic characteristics and fruit and vegetable availability. Exposures to vegetable flavours through breast milk may promote later child vegetable consumption.